Dynamics of Tax Revenue Across Business Sectors and Taxpayer Categories: A Mixed-Design ANOVA Approach - Chantha, Kong (Cattleya Darmaya Fortuna, 2026)
This study examines the dynamics of tax revenue in Banteay Meanchey Province, Cambodia, by analyzing the effects of business sector, taxpayer category, and their interactions. Using a mixed-design ANOVA, it analyzes tax revenue from small and medium taxpayers in the Industry, Services, and Agriculture sectors during 2017–2024. The results show significant sectoral differences, with Services and Industry generating substantially higher revenue than Agriculture, reflecting greater formalization, capital intensity, and profit orientation. The taxpayer category effect is nuanced: small and medium taxpayers do not differ significantly in isolation, but after controlling for sectoral composition, small taxpayers contribute significantly less revenue than medium taxpayers, indicating sector-dependent contributions. Interaction effects further reveal that both small and medium taxpayers in Industry and Services outperform their agricultural counterparts, underscoring the amplifying role of sectoral context in revenue generation. Temporal effects are largely insignificant; however, the sharp decline and uneven recovery observed in 2020, associated with the COVID-19 pandemic, highlight the importance of sectoral and taxpayer heterogeneity in fiscal resilience. Overall, the findings support a differentiated, sector-sensitive tax policy that prioritizes medium taxpayers in Services and Industry as core revenue anchors and incorporates sector–taxpayer interactions.